2010
DOI: 10.1103/physrevlett.104.070802
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Comparison of Two High-AccuracyAl+Optical Clocks

Abstract: We have constructed an optical clock with a fractional frequency inaccuracy of 8.6x10{-18}, based on quantum logic spectroscopy of an Al+ ion. A simultaneously trapped Mg+ ion serves to sympathetically laser cool the Al+ ion and detect its quantum state. The frequency of the {1}S{0}<-->{3}P{0} clock transition is compared to that of a previously constructed Al+ optical clock with a statistical measurement uncertainty of 7.0x10{-18}. The two clocks exhibit a relative stability of 2.8x10{-15}tau{-1/2}, and a fra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
824
0
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 881 publications
(842 citation statements)
references
References 42 publications
7
824
0
11
Order By: Relevance
“…In our setup two fused silica windows are 25 mm away from the atoms and have a radius of 38 mm and a thickness of 12 mm. We estimated a capacitance of 0.6 pF between the two surfaces and a time constant of ∼50 d assuming a high resistivity of 10 18 Ωm for fused silica [51]. We have operated our vacuum system for more than 3 years and possible charges present at the begin ning should have decayed to give a Stark shift <1 10 17 × − that we take as uncertainty.…”
Section: Other Shiftsmentioning
confidence: 99%
“…In our setup two fused silica windows are 25 mm away from the atoms and have a radius of 38 mm and a thickness of 12 mm. We estimated a capacitance of 0.6 pF between the two surfaces and a time constant of ∼50 d assuming a high resistivity of 10 18 Ωm for fused silica [51]. We have operated our vacuum system for more than 3 years and possible charges present at the begin ning should have decayed to give a Stark shift <1 10 17 × − that we take as uncertainty.…”
Section: Other Shiftsmentioning
confidence: 99%
“…From §1, it is seen that 27 Al + , 199 Hg + and 171 Yb + single trapped ion systems [24][25][26] and 87 Sr and 171 Yb atoms in a lattice [27,28] have already demonstrated systematic uncertainties below that of primary Cs. In the 27 Al + case, a relative frequency uncertainty of approximately 10 −17 has been achieved, together with an uncertainty of 10 −16 for 87 Sr atoms in a lattice.…”
Section: Possible Algorithms For a Redefinition Of The Secondmentioning
confidence: 99%
“…Recently, a second 27 Al + quantum logic clock was built with 25 Mg + as the logic ion, and comparisons between the two clocks have demonstrated a frequency uncertainty of approximately 9 × 10 −18 , with an instability of 2.8 × 10 −15 t −1/2 and a frequency difference between the clocks of −1.8 × 10 −17 [24]. With an observed ion linewidth of 2.7 Hz, this gives the highest atomic Q observed to date of 4.1 × 10 14 , and is currently the lowest frequency uncertainty for optical clock systems.…”
Section: Single Trapped Ion Optical Clocksmentioning
confidence: 99%
“…The frequencies of these transitions are typically in the (near-) infrared with linewidths below 10 Hz, which makes them amenable to high-resolution laser spectroscopy. Optical clocks based on trapped atomic ions have shown that laser spectroscopy at very high accuracy (below one part in 10 17 ) is possible [6]. Recent theoretical studies point out that also for molecular hydrogen ions experimental uncertainties in the 10 −16 range should be possible [7,8].…”
Section: Introductionmentioning
confidence: 99%